EFFECT OF LEUKOTRIENE RECEPTOR ANTAGONIST MONTELUKAST ALONG WITH CURCUMIN AGAINST GASTRIC ULCERATION (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Curcumin, a yellow pigment in the spice turmeric, has been used for centuries as a treatment for inflammatory diseases. This yellow pigment has anti-secretary property in different experimental ulcer models. Montelukast, a leukotriene receptor antagonist has been used for the treatment of inflammatory disease. This substance has antioxidant property in different experimental models. This data supports to evaluate the synergistic effect of Montelukast along with Curcumin against gastric ulceration. Gastric ulcers were induced by administering Aspirin (200 mg/kg) plus pylorus ligation and Indomethacin (20 mg/kg). Evaluation of Montelukast along with Curcumin was carried out in above experimental models. All the Montelukast (10 mg/kg) along with Curcumin (60 mg/kg) treated animals showed more significant reduction of ulcer index in both above experimental models compared to individual treatment with both, Curcumin and Montelukast.